(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
This study conduct to produce nutritious bread using locally abundant and available raw materials such as wheat, potato, soybean flour & oil. Potato ranks third in Bangladesh behind rice and wheat, in terms of total production. Potato is commonly used as a vegetable in Bangladesh, but in many other areas potato is treated as a staple food. Policy makers and administrators realize that, to meet the country’s growing food requirements, the dependence on cereals must be reduced. A bounty production of potatoes in Bangladesh should channelize to product diversification to legitimize the price of Potatoes will help the potato farmers. It is relatively labor-intensive and land-intensive and would combine well with other crops in cropping systems to use land that would otherwise be idle. A sharp revenue earning will be enjoyed for the Government provided potato diversified use occurs here in Bangladesh. This study was dedicated to very high share use of potatoes in various frequently used foods like bread. Trying to use upto 50% of potato to make various products like bread, cakes & potato flakes. The proximate analysis test or laboratory test shows containing protein 2.26% comparing with market breads 1%. The taste of bread produced in our laboratory was compared with other five company wheat breads, available in market. The product showed extraordinary softness & flavor relative to other market available breads. DOI: http://dx.doi.org/10.3329/bjsir.v48i3.17332 Bangladesh J. Sci. Ind. Res. 48(3), 201-204, 2013